Exchange Rate Dynamics: Evidence From Major Sub-Saharan Africa Oil-Exporting Countries - Abdullahi, Idris Abdulqadir (2019)
This study investigates the exchange rate dynamics in the selected 15 major oil-exporting sub-Saharan African countries namely, Angola, Cameroon, Chad, Congo Republic, Congo Democratic People Republic, Cote d'Ivoire, Equatorial Guinea, Gabon, Ghana, Malawi, Niger Republic, Nigeria, South Africa, Sudan, and Zambia. The working definition of exchange rate dynamic drawn from exchange rates economic related problems such as exchange rate fluctuations, exchange rate devaluation, and exchange rate pass-through. The findings from the first objective reveal evidence of a long-run relationship between the real exchange rate and macroeconomic variables in the selected countries. Nevertheless, the study also explores the dynamics of real exchange rate fluctuations and exchange rate fundamentals using pooled mean group, mean group, and fixed dynamic effect models. The results revealed evidence that real exchange rate fluctuations have a significant influence on the real exchange rate fundamentals, namely, terms of trade, trade openness, foreign direct investment, and government expenditure. The second objective of the study examined the effects of exchange rate devaluations on trade balances for the selected major oil-exporting countries using linear and nonlinear autoregressive distributed lag bounds testing and ECM.